2014
DOI: 10.1186/s12974-014-0156-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention rescues maternal obesity induced behavior deficits and neuroinflammation in offspring

Abstract: Obesity induces a low-grade inflammatory state and has been associated with behavioral and cognitive alterations. Importantly, maternal environmental insults can adversely impact subsequent offspring behavior and have been linked with neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (AHDH). It is unknown if maternal obesity significantly alters offspring sociability, a key ASD feature, and if altering maternal diet will provide an efficacious inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 85 publications
8
101
3
1
Order By: Relevance
“…Consistent with other reports, we detected increases in body weight, increases in leptin, but no differences in insulin levels or evidence of insulin resistance in the dams. (Guo and Jen, 1995; Kang et al, 2014; Srinivasan et al, 2006a,b) (Fig. 1A and B).…”
Section: Discussionmentioning
confidence: 85%
“…Consistent with other reports, we detected increases in body weight, increases in leptin, but no differences in insulin levels or evidence of insulin resistance in the dams. (Guo and Jen, 1995; Kang et al, 2014; Srinivasan et al, 2006a,b) (Fig. 1A and B).…”
Section: Discussionmentioning
confidence: 85%
“…Dietary intervention from before pregnancy or during lactation normalises the increased adiposity and circulating leptin, insulin and triglycerides in weanling offspring, rescues the altered motivation and hyperphagia and partially normalises glucose homeostasis and adipocyte morphology in adulthood (Bayol et al, 2007;Rodriguez et al, 2012;Zambrano et al, 2010). In addition, maternal dietary intervention rescues the increased anxiety and altered social behaviours in female offspring of maternal DIO mice in association with amelioration of central inflammation in these offspring (Kang et al, 2014). However, the same reversal is not seen in male offspring.…”
Section: Candidate Programming Mechanisms and Factors In Maternal Obementioning
confidence: 85%
“…Initial investigations using non-human primates reported that young adult female, but not male, macaques born to mothers fed a high fat diet showed increased anxiety to novel and threatening objects [27]. These findings were supported by rodent experiments that found more anxiolytic behaviors in the elevated plus maze and open field test in 1–3-month old male and/or female offspring born to dams fed a high fat diet before mating and during gestation and lactation compared to offspring born to dams fed a control diet [28,29,30,31]. However, weanling (e.g., post-natal day 23–45) rodents born to obese mothers or those fed a cafeteria diet during lactation exhibit lower levels of anxiety [32,33].…”
Section: Cognitive Function and Mental Health In Offspring Born Tomentioning
confidence: 88%